Unusual Presentation of Congenital Protein C Deficiency as Arterial Thrombosis along with Venous Thromboembolism - Khan, Tunaggina Afrin; Ahmed, Saiful; Abdullah, Abu Sadique; Alam, Mohammad Sarwar; Kabir, SM Eftarjahan; Haque, Mostashirul; Jannat, Sufia; Rahman, Aparna; Islam, Lohani M Tajul; Safiuddin, Mohammad (University Heart Journal, 2017)
Abstract not available University Heart Journal Vol. 12, No. 1, January 2016; 34-36